Urgent Prevention of Corona Virus Disease 2019 (COVID-19): Chinese Eating and Mask-Wearing Cultures - Cheng, Kang; Cheng, Vivien; Zou, Changhua (Journal of Public Health International, 2020)
Chinese people have a very good mask-wearing culture; it is normal to wear masks to protect their faces from wind and pollution. Thus, they easily accept the wearing of masks to prevent infectious diseases, as seen with the Corona Virus Disease 2019 (COVID-19) in China today. However, Chinese people have a dangerous eating culture: they share foods or soups from the same bowls and pots using their personal chopsticks/spoons and emphasize loud talking when eating at banquets or at homes. We think this eating culture has raised the infection risk of COVID-19 from person to person by contamination. Therefore, in this paper, we propose models to elucidate how people are infected with COVID-19 through droplet transmission when eating with Chinese cultural context to address the urgent need to change Chinese eating culture; we believe these study models can help not only the Chinese people, but also other national people, to raise mindfulness of public health, prevent COVID-19 and other infectious diseases, at the present pandemic and in the future.
Keywords: COVID-19; Droplet Transmission; Mask-Wearing; Eating Culture; Disease Prevention; China